RIWAYAT PAJANAN PESTISIDA SEBAGAI FAKTOR RISIKO KEJADIAN ABORTUS SPONTAN (Studi Pada Ibu Hamil di Puskesmas Sidamulya Kabupaten Brebes) - Ayu Rahayu; Rahayu Astuti; Sayono - (Universitas Muhammadiyah Semarang, 2015)
Background: The prevalence of abortion in Iran in 2014 reached 45.7% of the 2,470 pregnant women. Abortion among farmers exposed to pesticides as much as 9%. Pesticide exposure in pregnant women can cause thyroid dysfunction that causes hypothyroidism causing abortion. Methods: This case-control study involving 30 cases and 30 control in Puskesmas Sidamulya. The variables studied were history of pesticide exposure (duration of exposure, long exposure every day, duration of exposure every week, engaging in agricultural activity). And the incidence of spontaneous abortion, among the variables that cholinesterase levels. Analysis using Chi-square test. Results: There was a relationship with the exposure period the incidence of spontaneous abortion (p=0.001,OR=14.00 CI 95%), There is a relationship between duration of exposure every day with spontaneous abortion (p=0.001,OR=12.250 CI 95%), there is a relationship long exposure every week with Spontaneous abortion (p=0.000,OR=25.375 CI 95%), there is a relationship of involvement in farming activities with the incidence of spontaneous abortion (p=0.004,OR=7.875 95% CI) Conclusion: There is a relationship between the length of exposure with spontaneous abortion (p=0.001, OR=14.00 CI 95%), There is a relationship between duration of exposure every day with spontaneous abortion (p=0.001,OR=12.250 CI 95%), There is a relationship Exposure every week with spontaneous abortion (p=0.000,OR=25.375 CI 95%), There is a relationship of involvement in agricultural activities with spontaneous abortion (p=0.004, OR=7.875 95% CI)Keywords: incidence of spontaneous abortion, history of exposure to pesticides